Investigation of the geometry modeling of metal organic halide vapor phase epitaxy (MOHVPE) reactor - Annuar, N.Z.M.; Sabri, M.F.M.; Bakar, A.S.A. (Trans Tech Publications, Switzerland, 2013)
The new approach for designing a horizontal metal organic halide vapor phase epitaxy(MOHVPE) reactor chamber is proposed. The model is conjugated with comprehensive detailed simulation for horizontal tube reaction chamber by using computerized software. The modeling approach is based on the hybridization of MOCVD and HVPE. The development consists of 5 inlet nozzles with dimension of 54 cm long. The numerical study of horizontal MOHVPE growth shows dependence on temperature and species flow rates. The inlet area is set to room temperature while the whole chamber is set in the temperature range from 1273 K to 1473 K. It is seen that the flow pattern is influenced more by the temperature distribution and geometry of the chamber.